Traditional Palembang Society Wisdom on Natural Resource Management for Food Security - Sasua Hustati Syachroni; Asvic Helida (Journal of Global Sustainable Agriculture, 2022)
Studies on managing natural resources are currently attracting high interest in research. This is driven by the desire to find solutions to the problems that arise in managing natural resources to meet the needs of human life. Population increase and growth have caused the use of natural resources to be increasingly depleted, even close to scarcity. This research aims to reveal the forms of traditional wisdom of the people of Palembang in managing their natural resources to achieve their food sovereignty. The study was conducted on the people of Palembang City in December 2018. The research method is a qualitative descriptive method based on the analysis of data obtained in the field. The study results show that there is traditional wisdom in Palembang related to utilizing natural resources, including lebak lebung, bekarang iwak, ngaben, culinary pempek, and bekasam. This conventional wisdom is closely related to natural resource management, which increases food sovereignty. Traditional knowledge in Palembang society has two forms which are described as follows. First, local wisdom is in the form of Bekarang Iwak and Lebak Lebung. Conventional wisdom every year is still carried out by the people who live along the river as a form of natural resource management. Second, traditional knowledge in the form of culinary, which plays a role in fulfilling national food needs, namely pempek and bekasam culinary.